Rejecting the Neoliberal Balkan Land Grab Hypothesis: The Absence of the EU's Transformative Power in Land Use Governance in Bosnia and Serbia. Issue 2 (4th March 2021) - Parramore, Sean; Webb, Jonathan
ABSTRACT: Amidst doubts that it still has transformative power to drive institutional change in the Balkans, structuralists claim that the 'neoliberal' European Union (EU) helps enable 'land grabbing' by driving the region to liberalize land governing institutions. Based on our field research in urban contexts we reject this supposed causal relationship. We examined the processes that enabled two recent high-stakes land deals in the capitals of Serbia and Bosnia–Herzegovina, both Balkan countries seeking EU accession. Using the Institutional Analysis and Development framework, we find the EU's transformative power absent in both cases. Instead, we observe national and local elites opaquely facilitating hand-picked investments and cooperating to change urban land-use rules. We thus argue that endogenous drivers, like the possibility of expanding rent-seeking in situations of unequal information access, better explain the Balkan land deal phenomenon; and that the generalization that the 'neoliberal' EU helps drive land grabbing needs serious reconsideration.